(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The article presents a characteristic of the distribution of moth butterflies (Pyralidae, Crambidae) in agrocenoses of the Ferghana Valley by plant families and life forms. 22 species of butterflies have a trophic relationship with 30 species of cultivated plants belonging to 10 families. There are 18 species in cultivated herbaceous plants, 3 species in trees, and 1 species in shrubs.